A travessia do analógico para o digital: as mudanças no processo de produção de notícias na TV Paraíba - Lima, Luciellen Souza (2015)
For a few years now it has been taking place a an intense digitalization on Brazilian television, stimulated mainly by the implantation of digital TV in Brazil. Since the beginning of digital transmission in the country in 2007, TV stations began to worry about replacing analogical equipment, still part of the news production process and transmission, for the digital type. This shift from one technology to another brings technical changes to production routines and numerous possibilities of transformation in the way the news will be delivered. Amidst this scenario, producers of journalistic content grope in a transition full of uncertainties. This research was based on the experience at TV Paraíba, TV station affiliated to Rede Globo, in the city of Campina Grande, Paraíba, which completed its full digitization process in 2013. The study focuses on the changes in news production process caused by the gradual retirement of analogical technologies. We transform this study into a series of news reports for television so that this written text corresponds to the final report of the product. The recordings accompanied the shift from analogical to digital at TV Paraíba, including expectations, difficulties encountered, changes in routines and the attitude of journalists towards the new tools. In order for that to be accomplished, we combined journalistic and scientific techniques in a constructive experience. This final report describes the path taken to build the series of news reports, besides bringing an academic / bibliographic study on the theme.